The art of walking - Daniels, Tim; Hilliard, Michael (Michael Christopher) (Online access: Alexander Street Press Environmental Studies In Video Outside North America., 2010)
Follow in the footsteps of three remarkable people - American environmentalist and Ê»PlanetwalkerÊ¼ John Francis; former German figure skater Katarina Witt; and Australian Paralympian skier Michael Milton - each with equally inspiring stories, as they begin their trek along AustraliaÊ¼s most spectacular coastline, the Great Ocean Walk. The Great Ocean Walk is one of the most beautiful walks in the world. It runs 104 kilometers from Apollo Bay to a landmark known as the Ê»12 ApostlesÊ¼, highlighting the diverse and rugged landscapes of southern Victoria. John Francis became known as 'the Planetwalker' after seeing the environmental destruction caused by two tankers that collided beneath the Golden Gate Bridge in 1971. It had such an immense effect, that he decided to give up using all forms of motorized vehicles. In 1982, when he began a walking and sailing pilgrimage around the world, he founded Planetwalk, a non-profit educational organization dedicated to raising environmental consciousness and promoting earth stewardship. For almost three decades now, he has travelled the world on foot, rediscovering the rhythms in nature and spreading a message of environmental respect and responsibility. On the journey, we discover JohnÊ¼s philosophy on life - that to experience the spirit of the place, you need to take the time to experience and listen to whatÊ¼s around you. Katarina Witt is best known as the free-spirited figure skater that won two gold medals for Germany in the 1980Ê¼s. Her competitive record makes her one of the most successful figure skaters of all time. But nowadays she walks a different path through life. Apart from her role as a TV host, Katarina has set up a foundation to help children with disabilities. As she continues the journey, Katarina believes there is an Ê»artÊ¼ to walking - that by keeping your eyes open and seeing whatÊ¼s around you, seeing what nature has created and being thankful for your life. Michael Milton is Australia's fastest Paralympian skier, and first ever winter gold medalist. Since he lost his leg to bone cancer at age 9, he has continued to conquer the most unimaginable of feats, to simply prove to himself and his doubters that he can. He has hiked Mt Kilamanjaro, walked the Kokoda Track twice, and represented Australia at the Beijing Olympics, as a cyclist. Michael feels that by experiencing the beautiful and rugged scenery on the walk, he now has a sense of rejuvenation, a feeling of being alive, and a sense of peace. He meets a local aboriginal elder who teaches him about the benefits of listening to nature and the spirit of the land. Join them and experience the walk along blank canvas-like pristine white beaches, through forests of humbling 60-metre Mountain Ash trees, and beneath giant, sculpted limestone pillars carved over centuries by crashing ocean surf. See how the simple act of walking is transformed into something far more powerful - make your own journey and discover what is uniquely yours.